Development of Research Instruments as A Measure of Literacy in Analyzing Nutritional Problems in Toddlers among Posyandu Cadres - Oktaviani Cahyaningsih; Dewi Sari Rochmayani (Indonesian Journal of Global Health Research, 2025)
Literacy in the context of nutritional issues in toddlers is the ability to understand concepts, apply them, and make decisions based on the science of nutrition and child health in a scientific, rational, and responsible manner to solve problems in daily life. Cadres, as one of the human data sources in the community and involved in health promotion and intervention efforts, need to develop literacy in studying how food and nutrients affect the growth, development, and health of toddlers. Toddler nutrition issues such as stunting, underweight, wasting, anemia, and obesity not only affect the physical condition of children but also their cognitive development and long-term performance. The development of research instruments needs to be carried out as a measure of the extent to which cadres understand nutritional issues in toddlers, which remains a serious problem in Indonesia. Objective: The development of this instrument aims to provide an overview and guidelines for developing health modules that can be used to train posyandu cadres in assisting government programs to reduce nutritional problems in toddlers. Method: The process of developing this instrument consists of stages: 5 phases, namely 1) Initial investigation, 2) Design, 3) Construction/development, 4) Testing (test, evaluation, and revision), and 5) Implementation. Content validity test with Aiken's V coefficient, instrument validity is conducted using the product moment correlation method, while the reliability test is conducted using the Cronbach's Alpha method. Results: Each item of the research instrument to be used shows the following results expert construct validity test using Aiken's V coefficient value with results ≥ 0.80 and all item questions having Sig. < 0.05, it can be concluded that each question item is positively correlated and valid, while for the reliability interpretation results Reliability shows a Cronbach’s Alpha value of 0.932 > 0.361, thus it can be concluded that the research instrument has high reliability (reliable). Conclusions: Content validity test with Aiken's V coefficient, instrument validity is conducted using the product moment correlation method, the development of this research instrument uses The validity test with Aiken's V coefficient shows that each item is valid. Pearson Product Moment is used to test the validity of the instrument, while Cronbach's Alpha is used to test the reliability of the instrument. while the reliability test is conducted using the Cronbach's Alpha method.